1989
DOI: 10.1093/schbul/15.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use in Young Adults With Schizophrenic Disorders

Abstract: Use of nonprescribed mood altering substances is pervasive and problematic in young adults with serious mental illnesses in community care. Fifty-eight percent of young adult clients with clearly defined schizophrenia or schizophrenia-related disorders participating in a long-term community treatment study were rated by staff or themselves as using alcohol, cannabis, or other street drugs several times a week or more. We interviewed in depth a random sample of these "significant users" to obtain their perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
1
8

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(139 citation statements)
references
References 22 publications
7
123
1
8
Order By: Relevance
“…Co-morbid individuals with family members who are not users often distance themselves from their families when they begin substance use (Test, Wallish, Allness, & Ripp, 1989;Drake et al, 1998). In their stead, mutual substance use can form a basis for new friendships, especially for those who might otherwise have trouble socializing due to mental illness symptoms (Drake et al, 1998).…”
Section: How Social Network and Social Support Systems Mattermentioning
confidence: 99%
“…Co-morbid individuals with family members who are not users often distance themselves from their families when they begin substance use (Test, Wallish, Allness, & Ripp, 1989;Drake et al, 1998). In their stead, mutual substance use can form a basis for new friendships, especially for those who might otherwise have trouble socializing due to mental illness symptoms (Drake et al, 1998).…”
Section: How Social Network and Social Support Systems Mattermentioning
confidence: 99%
“…Test, Wallisch, Allness, and Ripp (1989) reported that 86% of their patients with schizophrenia drank coffee, averaging 6 cups per day; this quantity has been associated with caffeine withdrawal and related disorders (American Psychiatric Association, 1994). In contrast, only 9% of the general population consumes as much caffeine (Greden, Fontaine, Lubetsky, & Chamberlain, 1978).…”
Section: Licit Substance Use Among Psychiatric Outpatients: a Qualitamentioning
confidence: 99%
“…Among all persons with a diagnosis of schizophrenia, 47% meet lifetime criteria for a substance use disorder (Regier et al, 1990). This prevalence rate is often higher in samples of schizophrenic patients in treatment (Mueser et al, 1990;Test, Wallisch, Allness, & Ripp, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Among all persons with a diagnosis of schizophrenia, 47% meet lifetime criteria for a substance use disorder (Regier et al, 1990). This prevalence rate is often higher in samples of schizophrenic patients in treatment (Mueser et al, 1990;Test, Wallisch, Allness, & Ripp, 1989).A diagnosis of substance abuse or dependence impairs both the process and outcome of mental health treatment. Symptom exacerbation and psychiatric admissions have both been linked to acute drug use in outpatients with a severe and persistent mental illness (SPMI), such as schizophrenia (Haywood et al, 1995;Shaner et al, 1995).…”
mentioning
confidence: 99%